Crystal structure of nickel manganese-layered double hydroxide@cobaltosic oxides on nickel foam towards high-performance supercapacitors - Peng, Huihua; Jing, Chuan; Chen, Jie; Jiang, Deyi; Liu, Xiaoying; Dong, Biqin; Dong, Fan; Li, Shaochun; Zhang, Yuxin (CrystEngComm, 2019)
Rational design of the crystal structures of electrode materials is considered as an important strategy to construct high-performance supercapacitors. Herein, the three-dimensional crystal structure NiMn LDH@Co 3 O 4 composites on Ni foam with different feeding Ni/Mn molar ratios were well-designed with hydrothermal, calcination and co-deposition methods, wherein urea hydrolysis supplied the alkali and carbonate ions. The electrochemical properties of the produced electrode materials were analyzed by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), electrochemical impedance spectroscopy (EIS) and cycling stability tests using 6 M KOH electrolyte. Indeed, the optimal feeding Ni/Mn molar ratio was determined to be 3 : 1. The resulting electrodes exhibited maximum specific capacitance (607.9 F g −1 at 0.5 A g −1 ), respectable rate capability and excellent cycling stability with less than 3% loss of capacitance after 1000 cycles, which could be ascribed to the well-designed core-shell architecture and ultrathin nanosheets structure of LDH. As for practical application, the asymmetric supercapacitor assembled using NiMn LDH@Co 3 O 4 as the positive electrode and activated graphene (AG) as the negative electrode was also evaluated, which demonstrated a high energy density of 26.49 W h kg −1 at the power density of 350 W kg −1 . The findings suggest that the three-dimensional crystal structure NiMn LDH@Co 3 O 4 composites have potential application as promising electrode materials for energy storage devices or other applications. Rational design of the crystal structures of electrode materials is considered as an important strategy to construct high-performance supercapacitors.